Disaster risk reduction in conflict contexts: Lessons learned from the lived experiences of Rohingya refugees in Cox's Bazar, Bangladesh. (November 2020) - Zaman, Shamrita; Sammonds, Peter; Ahmed, Bayes; Rahman, Taifur
Abstract: Bangladesh is currently hosting more than one million stateless Rohingya refugees, who fled from the Rakhine State to avoid genocide and serious crimes against humanity persecuted by the Myanmar Army. The newly arrived Rohingyas were accommodated in overcrowded refugee camps in Cox's Bazar District (CBD). The camps are highly vulnerable to landslides, tropical cyclones, flash-flooding, and communicable disease outbreak. Although a number of improvement measures are ongoing, however, no study to date has addressed Rohingyas' self-adopted strategies to mitigate disaster risks. Consequently, this paper aims to explore how refugees cope with risks associated with environmental hazards in the Kutupalong Rohingya Camp in CBD. A mixed-methods research strategy incorporating both quantitative household questionnaire survey and qualitative focus group discussions (FGDs) techniques were applied. In total 250 Rohingya refugees were selected for the questionnaire survey using a stratified random sampling method from camps 17 and 19, and two FGDs (male and female-only) were carried out in camp 13 involving 21 Rohingya participants. Results derived from the study show that responding to early warning systems, storing dried food and medicine, utilising available resources, relocating to safer shelters, and keeping hopes high were some of the coping strategies practised by the respondents. Literacy level imposed a significant impact over respondents' perception to accept various measures. For instance, the probability of storing dried food in preparation for disasters was 4 times higher among literate Rohingya compared to their illiterate counterparts. Similarly, for literate respondents, the probability was 20 times higher to store medicine than for illiterate. Guaranteed distribution of shelter strengthening kits among all refugee households, the inclusion of disaster risk awareness and preparedness training, ensuring safe and dignified return in Myanmar, and global and regional cooperation to address the refugee crisis are some of the propositions recommended in this study for improving Rohingyas' future adaptation strategies in a humanitarian context.